1992
DOI: 10.1073/pnas.89.15.6924
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Ras-dependent extracellular signal-regulated protein kinase (ERK) cascade.

Abstract: The small GTP-binding protein Ras appears to be required for transformation and differentiation induced by tyrosine kinases. The Ras requirement may be limited to a few tyrosine kinase-regulated signaling pathways or may be universal for all tyrosine kinase actions. Because both Ras and the microtubule-associated protein 2 kinases ERKi and ERK2 have been implicated in events that lead to neurite outgrowth, we explored the possibility that Ras and ERKs may lie on the same signaling pathway. Uzing PC-12 rat adre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
104
2
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(110 citation statements)
references
References 33 publications
3
104
2
1
Order By: Relevance
“…Ras plays a major role in integrating the signaling between the receptors and the kinase modules since the expression of a dominant negative, competitively inhibitory mutant of Ras, (N17-Ras) inhibits Raf-MKK-ERK signaling in diverse cell types (de VriesSmitts et al, 1992; Robbins et al, 1992;Thomas et al, 1992;Wood et al, 1992). Raf-1 is the most predominant upstream kinase that is involved in the activation of MKKs (Dent et al, 1992;Howe et al, 1992;Kyriakis et al, 1992).…”
Section: Map Kinase Kinase-1 and Map Kinase Kinase-2mentioning
confidence: 99%
“…Ras plays a major role in integrating the signaling between the receptors and the kinase modules since the expression of a dominant negative, competitively inhibitory mutant of Ras, (N17-Ras) inhibits Raf-MKK-ERK signaling in diverse cell types (de VriesSmitts et al, 1992; Robbins et al, 1992;Thomas et al, 1992;Wood et al, 1992). Raf-1 is the most predominant upstream kinase that is involved in the activation of MKKs (Dent et al, 1992;Howe et al, 1992;Kyriakis et al, 1992).…”
Section: Map Kinase Kinase-1 and Map Kinase Kinase-2mentioning
confidence: 99%
“…The MAP kinases or ERKs are downstream elements of the NGF signaling cascade that are activated by a Ras-dependent pathway (Robbins et al, 1992). To assess the capacity of the Trk mutants to regulate this pathway, we compared NGF-mediated activation of MAPK by Western blotting with an antiactive MAPK-antibody.…”
Section: Activation Of Downstream Signaling Elementsmentioning
confidence: 99%
“…Extensive studies in the last several years have demonstrated that the members of mitogen activated protein kinase (MAPKs) family constitute a superfamily of proteins that include extracellular-signalregulated protein kinases (Erks) and c-Jun N-terminal kinases/stress-activated protein kinases (JNKs/SAPKs) and P38 kinase (Boulton et al, 1990(Boulton et al, , 1991Davis, 1994;Kyriakis et al, 1994;Robbins et al, 1992). These kinases belong to the activated serine/threonine kinases, which are uniquely identi®ed by the ThrXaa-Tyr dual-phosphorylation motif, where Xaa is Glu, Pro and Gly for Erks, JNKs/SAPKs and P38 kinase, respectively (Cobb et al, 1994;Kallunki et al, 1994;Sluss et al, 1994).…”
Section: Introductionmentioning
confidence: 99%